The use of hyaluronic acid in facial matching (Research, Society and Development, 2021)
Facial filling with hyaluronic acid is a minimally invasive procedure that has stood out positively over the years in the field of Aesthetic Biomedicine. Due to the great demand for non-surgical options, techniques related to the use of dermal fillers emerged in facial harmonization, which are capable of providing volume increase, symmetrical balance and restoration of facial contours, promoting rejuvenation. Objective: To carry out a literature review on the use of hyaluronic acid as a filler in facial harmonization within aesthetic extensions, as well as to analyze the complications affected by hyaluronic acid. Method: This was an exploratory and descriptive study. The construction of the review was made through a survey using scientific articles and periodicals, selected from the sources: Academic Google, PubMed and Scielo. Results: The most relevant articles were analyzed in order to obtain a better execution of the work, developing information about the literature on this topic. Conclusion: It is remarkable that the use of injectable hyaluronic acid is growing every day, and has a fundamental role in treatments for the prevention and management of aging, and through this it has been gaining a prominent place, thus improving physical, mental and social well-being of the patient.